Puncak Kulminasi dalam Dunia Tasawwuf: Sebuah Kajian Sufistik - Hairuddin Hairuddin (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2019)
This article discusses the world of tasawuf and its ins and outs. This article uses the Library Study method with a Descriptive Historical Qualitative approach. As for the main sources in writing this article are references which include the discussion of Sufis and tasawuf. The author concluded that Sufism was born of various factors with the aim of approaching the khalik after going through several stages and riyadhah. The culmination of the servant's approach to khalik will give birth: al-Fana, al-Baqa, al-Ittihad, al-Hulul, and Wihdatul Wujud known as the culmination of the culmination.